Effect of energetic ion beam irradiation on structural and optical properties of a-Si:H thin films - Goh, Boon Tong; Ngoi, Siew Kien; Yap, S.L.; Wong, C.S.; Rahman, Saadah Abdul (2013)
Hydrogenated amorphous silicon (a-Si:H) thin films deposited by radio-frequency plasma enhanced chemical vapor deposition were irradiated by an energetic argon ion beam source from a 3.3 kJ Mather type dense plasma focus device. The effect of the energetic ion beam irradiation on the structural and optical properties of a-Si:H thin films has been studied. The results show that irradiation of the energetic ion beam leads to the formation of Si nano-crystallites embedded within the amorphous matrix. This significantly improves the optical properties of the films, which include widening of the optical band gap and exhibiting wide range of photoluminescence (PL) emission spectra at room temperature. The correlations of the PL peak energy and intensity with the optical energy gap and crystalline volume fraction in the variation of number of shots are discussed.